A Cross-Tool Communication Study on Program Analysis Tool Notifications - Johnson, Brittany; Pandita, Rahul; Smith, Justin; Ford Robinson, Denae; Elder, Sarah; Murphy-Hill, Emerson; Heckman, Sarah; Sadowski, Caitlin (International Symposium on the Foundations of Software Engineering (FSE), 2016)
Program analysis tools use notifications to communicate with developers, but previous research suggests that developers encounter challenges that impede this communication. This paper describes a qualitative study that identifies 10 kinds of challenges that cause notifications to miscommunicate with developers. Our resulting notification communication theory reveals that many challenges span multiple tools and multiple levels of developer experience. Our results suggest that, for example, future tools that model developer experience could improve communication and help developers build more accurate mental models.